Pengaruh Sumber Daya Manusia dan Infrastruktur TUKS Terhadap Kinerja Operasional Bongkar Muat PT. Timah Tbk. - Agus Nur Wakil; Tini Utami; Evyana Diah Kusumawati (Politeknik bumi Akpelni, 2025)
This study is motivated by the importance of the role of human resources and infrastructure in supporting the smooth running of loading and unloading activities. The study aims to determine the impact of human resources and TUKS infrastructure on the operational performance of loading and unloading activities at PT Timah Tbk, Muntok, Barat. The research employs a descriptive quantitative approach, with the research population consisting of all 38 workers involved in loading and unloading activities. The F-test shows that human resources and TUKS infrastructure have a positive impact on the operational performance of loading and unloading activities, with an F-value of 13.568, which is greater than the F-table value of 3.27, and a significance level of 0.000. With an R value of 0.661, it is found that 43% of the operational performance of loading and unloading activities is influenced by human resources and TUKS infrastructure, while 56% is influenced by other factors such as weather and operational systems. Therefore, enhancing human resources through training and developing infrastructure are strategic steps to improve the efficiency and effectiveness of loading and unloading operations at PT Timah Tbk